Ecological, biophysical and production effects of incorporating rest into grazing regimes: A global meta‐analysis. Issue 12 (15th September 2019) - McDonald, Sarah E.; Lawrence, Rachel; Kendall, Liam; Rader, Romina
Abstract: Grazing can have considerable ecological impacts when managed inappropriately, however livestock production is a significant contributor to global food security and the removal of land from production is not always a viable option. Grazing management practices that incorporate periods of planned rest (i.e. strategic‐rest grazing) may be an alternative to grazing exclusion or continuous grazing that could achieve ecological and animal production outcomes simultaneously. We conducted a meta‐analysis of global literature to investigate how strategic‐rest grazing mediates ecological (i.e., plant richness and diversity), biophysical (plant biomass and ground cover) and production response variables (animal weight gain and animal production per hectare) compared to continuously grazed or ungrazed areas. Overall, total ground cover and animal production per hectare were significantly greater under strategic‐rest grazing than continuous grazing management, but biomass, plant richness, plant diversity and animal weight gain did not differ between grazing treatments. Increasing the length of rest relative to graze time under strategic‐rest grazing was associated with an increase in plant biomass, ground cover, animal weight gain and animal production per hectare when compared to continuous grazing. Synthesis and applications . Understanding both the ecological and animal production trade‐offs associated with different grazing management strategies is essential to make informed decisions about best‐management practices for the world's grazing lands. We show that incorporating periods of rest into grazing regimes improves ground cover and animal production per hectare and that these benefits are more pronounced with increases in the length of time land is rested for. This extended rest also improves biomass production and weight gain compared to continuous grazing systems. Based on these meta‐analyses, we recommend that future research considers the duration of rest compared to graze time in comparisons of grazing systems. Abstract : Understanding both the ecological and animal production trade‐offs associated with different grazing management strategies is essential to make informed decisions about best‐management practices for the world's grazing lands. We show that incorporating periods of rest into grazing regimes improves ground cover and animal production per hectare and that these benefits are more pronounced with increases in the length of time land is rested for. This extended rest also improves biomass production and weight gain compared to continuous grazing systems. Based on these meta‐analyses, we recommend that future research considers the duration of rest compared to graze time in comparisons of grazing systems.